The Impact of Aid and Macroeconomic Policy on Growth in Nigeria: A Bounds Testing Approach - USMAN, Nuruddeen; APINRAN, Martins O (Asian Economic and Financial Review, 2019)
This paper explores the impact of aid and macroeconomic policy on growth with Nigeria as a case study. Given its limited use in the aid efficiency literature on Nigeria, the autoregressive distributed lag (ARDL) model was applied in this study for time series data covering 44 years (1970-2014) in an attempt to expand the use of this approach and to check if a similar (negative) relationship is found between aid and growth. The results showed a positive correlation i.e. aid supports growth in Nigeria in the long-term. The other variables identified above and trends such as labour force and technological change were also found to be positive towards economic growth in the long-term, though governance showed an insignificant relationship. In the short-term, investment and policy were found to have a negative correlation on growth. More data on governance (before 1996) could be applied to expand the findings of this study and other measures of macroeconomic policy could be used to test if a similar result is obtained as principal component analysis was applied in this case. Given our findings, this paper recommends that the government of Nigeria should prioritize aid since it has been empirically found to support growth.